Transformasi Digital dan Kecerdasan Buatan (AI) dalam Penguatan Keberlanjutan Usaha UMKM di Indonesia : Kajian Literatur Sistematis 2021-2026 - Sakinah L; Nadiya Aufa; Ulfiyatus Sabila; Dellia Anjani; Zaenal Abidin (Jurnal Bisnis Inovatif dan Digital, 2026)
This study aims to review the literature on the role of digital transformation and artificial intelligence (AI) in strengthening the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia for the period 2021–2026. Using a systematic qualitative literature review method, this study synthesizes findings from national and international scientific journals, reports from government institutions, and credible academic sources. The results show that digital adoption—including e-commerce platforms, digital payment systems, and AI-based applications—significantly increases market reach, operational efficiency, and business resilience of MSMEs. AI-based technologies such as machine learning, chatbots, and data analytics have proven capable of reducing operational costs and improving decision-making accuracy. However, low digital literacy, limited capital access, and uneven digital infrastructure remain major barriers. Government support through programs such as Bangga Buatan Indonesia and collaboration with the technology sector are key to accelerating inclusive digital transformation. This study concludes that synergizing digital transformation with AI has the potential to become the main pillar of MSME sustainability in the digital economy era in Indonesia.